STATE-LEGAL AND ADMINISTRATIVE TRANSFORMATIONS IN ARMENIA (1991-2003) - MINASIAN, Edik (CENTRAL ASIA AND THE CAUCASUS, 2004)
Almost right after it declared its independence on 21 September, 1991, Armenia gained internation- al recognition (December) from the U.S., Russia, Canada, Rumania, and other countries. On 2 March, 1992, our republic became a full-fledged member of the U.N., and on 25 January, 2001,a member of the European Parliament. Literally from the moment it declared its sovereignty, Armenia began building an independent republic. It was unable to finance the immense volume of state functions inherited from the disintegrated Soviet Union on its own. At this difficult transition stage, a different state government system had to be created, which would make it possible to strengthen the country’s economic potential and independence, raise the people’s standard of living, and ensure the stable development of social relations.Forming new power bodies became an urgent need. This process began as early as May 1990, after elections to the Supreme Soviet of Armenia, which was still a Union republic. At that time, the country was undergoing the transfer from the old Soviet power structures to a new parliamentary form of government. In order to form a new state government system, several vitally important documents were adopted. For example, the new constitutional Law on Fundamental Provisions set forth the state government procedure and distributed power among the executive, legislative and judicial branches.1 On 1 August, 1991, the Law on the President of the Republic of Armenia was adopted.2 There is no doubt that it is an important step toward political stabilization, even though discussions about the expediency of this institution and the president’s powers are still going on. In November and December of the same year, laws On the Supreme Soviet and On the Administration Structure delimited the spheres of activity of the supreme power bodies.3